CESifo World Economic Survey August 2010 - Gernot Nerb; Anna Stangl (CESifo World Economic Survey, 2010)
World Economic Climate: World Economic Climate clouded over slightly - Economic Expectations: Economic expectations downgraded again but remain positive - Inflation: Stable price trend expected - Interest Rates: Short-term interest rates expected to rise less than formerly anticipated - Currencies: Euro appears slightly undervalued - Special Topic: Cross-border trade and investment
Keywords: 330; World Economiy Survey; World Economic Climate; Economic Expectations; Inflation; Interest rates; Currencies; Cross-border trade and investment